Postpartum Depression Among Women With Previous Infertility in Health Care Centers of Hamadan in 2018 - Matinnia, Nasrin; Yazdi-Ravandi, Saeid (International Clinical Neuroscience Journal, 2020)
Background: Childbirth is one of the important goals of family, so the infertility can cause many problems for the family. Therefore, the aims of the current study were the frequency of postpartum depression and evaluate the relationship between postpartum depression, socio demographic factors and quality of marital satisfaction in postpartum women with a history of infertility referring to health centers in Hamadan. Methods: This study was a cross-sectional study. The study population consisted of all primiparous women with a history of infertility referring to Hamadan health care centres in 2018, of which 240 were randomly selected according to the inclusion criteria during one year. Subjects were assessed by demographic and clinical information checklist, Edinburgh Depression Inventory (EPDS) and marital relationship quality scale (Revised Dyadic Adjustment Scale; RDAS). All statistical calculations were performed by busing chi square with SPSS-17. Results: Totally 152 out of 240 participants (63.3%), had a degree of depression, of which 57 (23.7%) had a mild depression, 63 (26.3%) had moderate depression and 32 (13.3%) had severe depression. According to result of the study, marital satisfaction in 23.3% (56), 37.1% (89) and 39.6% (95) were good, moderate and low respectively. The quality of marital relationship associated significantly with and postpartum depression (χ2=19.3,P<0.001). The results of the study showed that there was a significant relationship between age, occupation, educational level, duration of infertility and depression (P<0.05), but there was no significant relationship between ethnicity, insurance and depression (P<0.05). Conclusion: Regarding the results obtained in this study and comparison with existing studies, the infertility problem can cause mental and psychological disorders in women. It seems that the marital satisfaction and its relationship with different factors and the proper interventions by health care providers are necessary to prevent postpartum depression in these women.